The Effect of Third-Party Funds and Financial Ratios on Net Profit with Financing as an Intervening Variable - Rizky Ananda Utami; Zuhrinal M. Nawawi; Nur Ahmadi Bi Rahmani (Universitas KH. Abdul Chalim Mojokerto, 2025)
PT. Bank Mega Syariah Tbk is one of the Islamic financial institutions in Indonesia that plays an important role in supporting economic growth through fund mobilization and financing distribution. The bank’s financial performance is inseparable from its ability to manage Third Party Funds (TPF) and financial ratio indicators such as ROA, ROE, and NPF. Net profit, as the main measure of bank profitability, can be influenced by various factors, both directly and indirectly through intervening variables such as financing. Therefore, this study examines the effect of Third-Party Funds and Financial Ratios on Net Profit with Financing as an intervening variable at PT. Bank Mega Syariah Tbk during the period 2016–2024. The sample was determined using purposive sampling, resulting in 216 data points, with analysis conducted using descriptive statistics and Structural Equation Modeling (SEM). The results show that Third Party Funds (X₁) have a positive and significant effect on Financing (Z), Third Party Funds (X₁) have a positive and significant effect on Net Profit (Y), Financial Ratios (X₂) have a positive and significant effect on Financing (Z), Financial Ratios (X₂) have a positive and significant effect on Net Profit (Y), Third Party Funds (X₁) have a positive and significant effect on Net Profit (Y) through Financing (Z), and Financial Ratios (X₂) have a positive and significant effect on Net Profit (Y) through Financing (Z) at PT. Bank Mega Syariah. This study indicates that the bank’s success in mobilizing TPF and maintaining healthy financial ratios not only directly affects profitability but also improves financing performance, which ultimately strengthens net profit. In other words, proper fund management and risk management strategies are key to sustaining customer trust, strengthening liquidity, and enhancing the bank’s competitiveness in the Islamic banking industry.